IT SOLUTIONS FOR EFFECTIVE HEALTHCARE MANAGEMENT - Šebej, Matej; Štěrbová, Ludmila, 1957-; Antonovič, Vladan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
Why do the healthcare facilities incur debt? What troubles the managers most? In what conditions do the healthcare professionals work? Is there space for improvement? Is it possible to deliver higher quality care? Nowadays, the healthcare providers are looking for solutions, which could help them satisfy more patients, reach lower costs and therefore increase own financial results and answer the abovementioned questions. Key element of such a solution is a business intelligence system, which supports decision-making and aligns enterprise objects with its progress and improves the overall performance. The thesis elaborates on the topic of business intelligence software QlikView in selected hospitals, which already implemented or are about to implement the business intelligence software. The intention was to find out ways in which the software is used in the hospitals, what key performance indicators the software usually measures and what could be the possible opportunities for its further use in the selected facilities. Research results indicate that the software significantly increased the work efficiency and that it contributes to more effective hospital management. However, such improvement in efficiency has also its drawbacks, namely it is the higher price per personal licence in comparison to the other business intelligence software on the market. Research also confirmed the fact that only usage of such software alone will not help to improve the overall bad state of Slovak healthcare system -- systematic measures such as DRG system have to be implemented in the first place in order to also effectively use the business intelligence software.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses